2004
DOI: 10.1016/j.jvs.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of 6-mm straight grafts versus 6- to 8-mm tapered grafts for brachial-axillary dialysis access

Abstract: The results of this study show an advantage in terms of primary and assisted primary patency rates, and complication rate for upper arm grafts with diameter 6 mm to 8 mm over grafts with 6-mm diameter in a patient population younger than 70 years without diabetes. The finding of a similar secondary patency rate in both groups is probably due to the surveillance program with sequential measurement of access flow and prompt surgical treatment of stenosis. However, we needed twice the number of rescue procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Limited clinical studies suggested that 8- to 6-mm tapered grafts improved primary patency rate and decreased complications, compared with 6-mm straight grafts. Further studies are required to confirm these observations 152,153. Yet another approach is to create a cuffed geometry made of ePTFE at the venous anastomosis to reduce regional turbulence, as venous cuffs seems to be beneficial in the arterial–arterial bypass ePTFE graft setting.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Limited clinical studies suggested that 8- to 6-mm tapered grafts improved primary patency rate and decreased complications, compared with 6-mm straight grafts. Further studies are required to confirm these observations 152,153. Yet another approach is to create a cuffed geometry made of ePTFE at the venous anastomosis to reduce regional turbulence, as venous cuffs seems to be beneficial in the arterial–arterial bypass ePTFE graft setting.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…6,8,15,[19][20][21] Although prosthetic AVGs are often placed in the upper extremity, they vary with respect to location, configuration, material, feeding artery, and draining vein. 1,[4][5][6][7]15,[22][23][24][25][26][27] The optimal graft location (upper arm or forearm) and graft configuration (straight or looped) are unknown. 5,28,29 Placement of an fAVG has the advantage of preserving upper arm veins for a future upper arm access site and may increase the suitability of upper arm veins for future upper arm AVF.…”
mentioning
confidence: 99%
“…4 The elements which take part in the development of NH (␣-smooth muscle actin positive cells derived from adventitial fibroblasts, extracellular matrices, a variety of growth factors and neovascularization) are well known, [5][6][7] but the true cause of the activation of these components remains unclear and is still under debate. Actually, NH prevention strategies (mechanical design of the graft, [8][9][10][11][12] biological reagents, [13][14][15] small-molecule drugs 16 ) have not produced the expected results essentially because they have not intervened on the initial causes. Using synthetic vascular prostheses in AVGs, most commonly made from expanded polytetrafluoroethylene (ePTFE), the first observation we could make was that the flow induced vein-wall vibration at the anastomosis site 17 where there was also large mismatch compliance between the vein and the graft wall.…”
mentioning
confidence: 99%